Incapsulatori anaforici e discorso riportato nell'italiano giornalistico: sfruttamenti coesivi della dimensione enunciativa - Pecorari, Filippo (My University, 2015)
This paper examines the interactions between anaphoric encapsulation and reported speech through the analysis of examples taken from a corpus of Italian news. Encapsulation may be realised by nominal, pronominal or null expressions and allows the writer to establish a new discourse referent through hypostasis, i.e. the reification of a co-textual portion. Cohesive strategies involving reported speech intrinsically act on the enunciative dimension, as defined by the Basel Model (Ferrari 2010a, 2014): it is the organizational dimension of the text that accounts for the relationship between different viewpoints in the textual units. We propose a two-output classification, where encapsulators are mainly distinguished according to their position (outside or inside reported speech) and to the nature of their antecedent (a simple reported speech or a global discourse reproduction). We particularly focus on two aspects of the encapsulators under examination: the interactions with persuasive (or pseudo-persuasive) effects and the specification of the source of the utterance in the sentence containing the anaphor.
Keywords: anaphora; anaphoric encapsulation; textual cohesion; reported speech; enunciative dimension; journalistic language; persuasion